Game of scones (Scholastic, Inc, 2021)
"An all-new original series featuring the art of viral sensation Joe Whale, AKA the Doodle Boy, and fan-favorite Eric Luper! Somewhere deep within the walk-in pantry at Belching Walrus Elementary lives an array of different foods that live in harmony. One day, the Supplies from the principal's office show up and insist on sharing the coolness of the cooler. Their ruler is a ruler (pun intended) named Baron von Lineal. There's plenty of room in the cooler for everyone, right? Wrong! It's up to three young heroes, Slice, Scoop, and Totz to venture out of the pantry and foil the Baron's plan for good. Highly illustrated with big black-and-white pictures from Joey on every page, this series will be sure to resonate with kids worldwide!"--Page [4] of cover.